Biska Jatra: Myth, Sign, Significance and Bhaktapur - Phelu, Rajan (Bagiswori Journal, 2022)
The still living ancient festivals which are mysterious, colourful and fun evolved in course of time due to the highest popularity of the paramount deities belonging to the two great religions: Hinduism and the Buddhism. Their rites and rituals possess the background of interesting myths, delightful legends, and captivating folktales. Every year, the Newars celebrate wonderful fairs and festivals on different auspicious days in Bhaktapur. Every festive event of Bhaktapur has its own specialties. This study examines myths and current practice of Biska Jatra in the cultural backdrop of Bhaktapur from the perspective of semiology. The common belief is that celebrating the festival will ward off evil spirits and dangers, boost growth in agriculture production and the economy; maintain peace and prosperity and ensure the protection of the country from the outside invaders. This study argues that the celebration of Biska Jatra depicts its rationality and significance in the socio-cultural lives of the residents of Bhaktapur.